Предмети озброєння та військового спорядження з Чорнівського городища ХІІІ ст. (дослідження 2018-2019 рр.) - Калініченко, Віталій; Ільків, Микола; Пивоваров, Сергій (Львів, Простір-М, 2020)
In the article the authors conduct a comprehensive analysis of weapons and military equipment found during the research of the Chornivka hillfort of the 13th century. The classiﬁcation of various types of arrowheads, parts of a belt set, jewelry, etc. is carried out. In addition, items that belong to the rider’s equipment are characterized. It is established that the found objects play an important role in the study of the military-political history of the Siret-Dniester interﬂuve in the Middle Ages.
Weapons and military equipment from the Chornivka hillfort of the 13th century (research of 2018-2019)
Weapons and military equipment from the Chornivka hillfort of the 13th century (research of 2018-2019)
Keywords: Чорнівське городище; середньовіччя; предмети озброєння; наконечники стріл; спорядження вершника; поясна гарнітура